Comparison of ascites fluid culture methods in patients with spontaneous bacterial peritonitis - J. Sedef BENGİSUN and Eyüp SELVİ and Elif ARIBAL and Şükran YAVUZDEMİR and Haluk ATAOĞLU and Selim KARAYALÇIN (Turkish Journal of Gastroenterology, 2020)
-